The moderating effect of ownership structure between the relationship of corporate social responsibility and firm performance in the ASEAN-5 - Avila, Mari Luis Augustin T. (Animo Repository, 2021)
Corporate Social Responsibility (CSR) is a business model, which encourages firms to invest in activities that not only benefit the firm and its stakeholders, but the society and environment as well. Several studies have pointed to the fact that increased CSR activities result in a potential increase in firm performance. However, the approval and execution of a firm’s CSR activities may differ depending on the ownership structure due to the varying expectations and opinions of shareholders. Thus, the study analyzes whether large or foreign shareholder ownership moderates the relationship between CSR and firm performance using structural equation modeling (SEM) analysis for a sample of large, non-financial firms in the ASEAN-5 consisting of 520 firm-year observations for the time period 2015 to 2019. Our empirical results show that firstly, there is a significant relationship between CSR and firm performance. Secondly, large shareholder ownership has a moderating effect between the relationship of CSR and firm performance. Thirdly, foreign shareholder ownership has a moderating effect between CSR and firm performance. Based on the results, given that CSR has an effect on the financial performance of the firm and different ownership structures moderate the aforementioned relationship, it is important for stakeholders to look into the ownership structure of the respective company that they are investing in as this may affect the CSR activities of the firm. A firm’s level of CSR activities may, in turn, affect the financial performance of the firm, which would consequently have an effect on the potential return on investment of the stakeholders. This research serves as a guide for stakeholders or potential investors to aid them in their investment decisions.